Teachers’ Awareness about Inclusive Education in Punjab: A Descriptive Enquiry - Amjad Islam Amjad, Humaira Iqbal, Shah Syed Manzar-Abbas (JIE, 2024)
Inclusive education (IE) is part of world agenda and is a relatively new concept for Pakistani teachers. The aim of the study was to explore teachers’ level of awareness about inclusive education. A descriptive survey was conducted, and a self-tailored questionnaire was distributed among 37 standalone public secondary schools (1- 10 classes). Sample for the study was selected by using multimethod, multi-stage sampling techniques from tehsil Chunian of district Kasur (Punjab). Both descriptive and inferential statistics were used to analyse data. Study revealed that teachers’ overall awareness about IE was at moderate level.